A Novel Approach based on PSO and Coloured Petri Net for improving Services in the Emergency Department - Louhab, Zouaoui; Boufera, Fatma (Journal of Soft Computing Paradigm, 2023)
Congestion in the Emergency Department (ED) is a major problem in the hospital for patients and staff, due to the increased waiting times, length of stay, and medical errors, thus causing great losses to the hospital. Emergency services are essential in society, given the human need for them at any stage of life. The emergency department is characterized by the complex nature of its resources, as it consists of different parts. Many solutions are being proposed in order to solve the numerous problems in the ED, and to improve the quality of service. Researchers rely on many techniques such as optimization algorithms, simulations, data mining, and other methods to solve congestion. In this research, an approach based on PSO algorithm and coloured Petri net has been proposed. The emergency department is modelled using a coloured Petri net, and PSO algorithm is used to determine the human resources. Based on the results, the simulation model is modified, restarted, and the results are compared with the Benchmark model. This research helps decision makers in the ED to find appropriate solutions for human resources.